Characterization of land use, from a social, economic and environmental dynamics - Ceballos-Freire, Alvaro Javier; Muñoz , Diego Andrés; Benavides-Martínez, Iván Felipe; Tobar, Carlos Julio (Revista de Ciencias Agrícolas, 2024)
Lack of data regarding the agricultural activities in the area of Imués (Nariño, Colombia) has hindered understanding of current land uses and their impacts on natural resources, which causes this area to be considered one of the most arid in the region. To comprehend these processes, a description of the main land uses and agricultural and livestock production systems was made. This was carried out from a social, economic, and environmental dynamic through the characterization and typification of farms. Groups or clusters were constructed, which were previously subjected to qualitative statistical analysis, using the multiple correspondence factor analysis (MCAF) method. Subsequently, the hierarchical classification method was applied. The MCAF was able to establish four factors that were framed in the interaction of climate, altitude, and the productive component associated with it. Similarly, taking into account the social, economic, and environmental perspectives, it was determined that these groups, under their particularities and agricultural vocations, exert pressure on the territory's strategic ecosystems and diversity of flora and fauna. This makes their rural activities unsustainable. It was also found that there is a vocation for livestock exploitation and some minor species in the middle and high-altitude zones of the territory. However, it was established for other groupings that their major typologies were associated with conventional management without any planning. This generates negative impacts on soil resources, such as erosion and forest fragmentation, together with the expansion of the agricultural frontier.